Comparative Study of Viscosity Behaviour of Novel 1-Furyl-3-(substituted phenyl)-2-propene-1-one in Different Percentages of Solvents - H. Bhendkar, Amol; P. Deohate, Pradip; Doshi, A.G.; Raut, A.W. (Asian Journal of Chemistry, 2016)
The viscosities and densities of 1-furyl-3-(substituted phenyl)-2-propene-1-one (I-VI) in different percentages of dioxane-water, ethanol-water and acetone-water mixtures have been measured. The data have been used to calculate the relative viscosities and to measure molecular interactions in the solutions to compare the viscosity behaviour of 1-furyl-3-(substituted pheny)-2-propene-lone (I-VI) depending upon the presence of different susbstituents.